IMPLEMENTATION OF CHARACTER EDUCATION TO PREVENT ADOLESCENT DELINQUENCY - Haerudin; Mitra Sasmita, Rahma Dilla Zainuri, Siti Masruroh; Supian Ramli (Adisam Publisher, 2024)
A stage of human development known as adolescence separates childhood from maturity. It's too advanced to be referred to as childhood, but it can be considered adulthood. Adolescence is a time of both physical and psychological transformation. The reproductive system grows in tandem with physical growth, and teenagers will go through more intense psychological changes than earlier generations. Among other things, the pervasive instances of drug abuse, promiscuity, crime, fraudulent diplomas, and various violent acts point to the issue of moral decay in the educational system. Aside from that, a lot of young people don't exhibit admirable moral qualities like courtesy, kindness, tolerance, humility, helpfulness, and social solidarity. There are two ways that character education is utilized to prevent adolescent delinquency: Character education is imparted through extracurricular activities, habituation, and Teaching and Learning Activities (KBM). Religion, honesty, tolerance, discipline, diligence, inventiveness, patriotism, and curiosity are among the character traits imparted.